A precise measurement of the $W$-boson mass with the Collider Detector at Fermilab - Aaltonen, T; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Appel, J; Arisawa, T; Artikov, A; Asaadi, J; Ashmanskas, W; et al. (American Physical Society, 2013)
We present a measurement of the $W$-boson mass, $M_W$, using data corresponding to 2.2/fb of integrated luminosity collected in ppbar collisions at $\sqrt{s}$ = 1.96 TeV with the CDF II detector at the Fermilab Tevatron. The selected sample of 470126 $W→ eν$ candidates and 624708 $W→μν$ candidates yields the measurement $M_W = 80387± 12$ (stat) $± 15$ (syst)$ = 80387 ± 19$ MeV$/c^2$ . This is the most precise single measurement of the $W$-boson mass to date.